Derivation of a prototype asthma attack risk scale centred on blood eosinophils and exhaled nitric oxide. Issue 2 (6th August 2021) - Couillard, Simon; Laugerud, Annette; Jabeen, Maisha; Ramakrishnan, Sanjay; Melhorn, James; Hinks, Timothy; Pavord, Ian
Abstract : Reduction of the risk of asthma attacks is a major goal of current asthma management. We propose to derive a risk scale predicting asthma attacks based on the blood eosinophil count and exhaled nitric oxide (FeNO). Biomarker-stratified trial-level attack rates were extracted and pooled from the control arms of the Novel START, CAPTAIN, QUEST, Benralizumab Phase 2b, PATHWAY, STRATOS 1–2 and DREAM trials (n=3051). These were used to derive rate ratios and the predicted asthma attack rate for different patient groups. The resultant prototype risk scale shows potential to predict asthma attacks, which may be prevented by anti-inflammatory treatment.